Influence of fiber orientation and fiber content on properties of sisal‐jute‐glass fiber‐reinforced polyester composites. Issue 6 (15th October 2015) - Ramesh, Manickam; Palanikumar, Kayaroganam; Reddy, Konireddy Hemachandra
ABSTRACT: The incorporation of natural fibers with polymer matrix composites (PMCs) has increasing applications in many fields of engineering due to the growing concerns regarding the environmental impact and energy crisis. The objective of this work is to examine the effect of fiber orientation and fiber content on properties of sisal‐jute‐glass fiber‐reinforced polyester composites. In this experimental study, sisal‐jute‐glass fiber‐reinforced polyester composites are prepared with fiber orientations of 0° and 90° and fiber volume of sisal‐jute‐glass fibers are in the ratio of 40:0:60, 0:40:60, and 20:20:60 respectively, and the experiments were conducted. The results indicated that the hybrid composites had shown better performance and the fiber orientation and fiber content play major role in strength and water absorption properties. The morphological properties, internal structure, cracks, and fiber pull out of the fractured specimen during testing are also investigated by using scanning electron microscopy (SEM) analysis. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42968. Abstract :